An Ex Vivo Comparison of Stainless Steel Cables to a Non-metallic Polymer Cerclage Cable in an Equine Metacarpophalangeal Joint Arthrodesis Model - Kadic, Lawrence I.M.; Liu, Chin-Chi; Riggs, Laura M. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The aim of this study was to compare the monotonic tensile strength and fatigue strength of a stainless steel cable (SSC) compared to a human non-metallic polymer cable (NMPC) in an ex vivo metacarpophalangeal joint arthrodesis model lacking a dorsal plate application.An ex vivo experimental biomechanical equine cadaver limb study. Ten metacarpophalangeal joints were collected from five adult Thoroughbred horses, euthanatized for reasons unrelated to orthopaedic disease. Each pair of metacarpophalangeal joints was randomly instrumented with either a 1.7-mm SSC or a NMPC. Each construct was tested in cyclic loading followed by a single cycle to failure in axial compression. Displacement at a target load of 200 N over 500 cycles at 1 Hz was recorded prior to single-cycle to failure testing.In cyclic testing, the overall movement of the NMPC constructs was more than that of the SSC constructs (p < 0.0001). In single-cycle testing, the maximum load achieved at failure in the SSC constructs was higher compared to the NMPC constructs (p = 0.0002).The results of this study do not support the use of a NMPC as a palmar/plantar tension band for metacarpophalangeal joint arthrodesis in horses suffering from a suspensory breakdown injury, because the stability of the SSC constructs outweighs the potential benefits and ease of application of the NMPC. However, additional ex vivo studies should be conducted to compare both cable systems with dorsal plate application on the metacarpophalangeal joint.
Keywords: Fetlock arthrodesis; tension band; equine; biomechanical performance of implants